PENGARUH PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN DAERAH PADA KABUPATEN/KOTA DI PROVINSI ACEH TAHUN 2010-2012 - Junarwati Junarwati; Hasan Basri; Syukriy Abdullah (Jurnal Telaah dan Riset Akuntansi, 2013)
The purpose of this study is to examine the effect of Local Revenue and its components which include Local Taxes, Local Retribution, Zakat, Results of Local Investment, and Others Local Income on the local governments financial performance in Aceh. The population was districts/cities in Aceh Province and the unit of analysis of this study was the local government budget report (or financial statements) audited by Supreme Audit Agency (BPK). A total of 23 Local Government Financial Reports districts/cities in Aceh province with the observation period of 3 years, or 69 local government financial reports, where analyzed using the multiple linear regression model. The first finding indicates that Local Revenue affects the financial performance of the districts/cities in Aceh province. Furthermore, other results suggests that the components of the Local Revenue: Local Taxes, Local Retribution, Zakat, Results of Local Investment, and Others Local Income jointly have effect on the local  financial performance of the district/city in Aceh province.Keywords : Local Financial Performance, Local Revenue